The reinforcing effect of polydopamine functionalized graphene nanoplatelets on the mechanical properties of epoxy resins at cryogenic temperature. (April 2017) - Wu, Yeping; Chen, Maobin; Chen, Mao; Ran, Zhipeng; Zhu, Chunhua; Liao, Hong
Abstract: In order to obtain epoxy nanocomposites with excellent mechanical properties at cryogenic temperature, an efficient method to functionalize graphene nanoplatelets (GNPs) is proposed. Through a simple dip-coating procedure, the GNPs were first functionalized with deposition of polydopamine coating (PDA@GNPs). Then, using polydopamine as a bridge, the PDA@GNPs were modified with amine groups after polyetheramine T403 grafting (T403-PDA@GNPs). Fourier transform infrared spectroscopy, thermogravimetric analysis and X-ray photoelectron spectroscopy analyses proved the successful functionalization of PDA and polyetheramine T403 on the surface of GNPs. Adding 0.1 wt% T403-PDA@GNPs significantly improved the cryogenic tensile strength and impact strength of the epoxy nanocomposites by 34.5% and 64.5%, which showed greater reinforcing effect than the pristine GNPs (12.6% and 19.1%) and PDA@GNPs (26.3% and 50.1%). The results of dynamic mechanical analysis and scanning electron microscopy observations indicated that the PDA and further polyetheramine T403 functionalization improved the interfacial interactions between GNPs and matrix, which ensured the much improved mechanical properties.